Doctor, builder, soldier, lawyer, teacher, dancer, shopkeeper, vet: exploratory study of which eleven-year olds would like to become a doctor. Issue 1 (December 2015) - McManus, I.; Ng-Knight, Terry; Riglin, Lucy; Frederickson, Norah; Shelton, Katherine; Rice, Frances
Abstract Background Very little is known about the extent to which eleven-year olds might consider a career in medicine. This exploratory study therefore asked children and their parents about medicine as a possible career, looking also at the relationship to a range of background measures. Methods A longitudinal, three-wave, questionnaire study of students transferring from primary to secondary school (STARS), with data collection at primary school (wave 1; mean age 11.3 yrs), in the first months of secondary school (wave 2; mean age 11.7 yrs) and at the end of the first year of secondary school (wave 3; mean age 12.3 yrs). Parents/carers also completed questionnaires. Children were entering ten large comprehensive secondary schools in the south-east of England; 46.3 % were female, 15.6 % receiving free-school meals, 39.8 % were Black or Minority Ethnic and 28.8 % had a first language which was not English. Of 2287 children in the study, 1936 children (84.5 %) completed at least one questionnaire of the three waves (waves 1, 2 and 3). The main outcome measures were an open-ended question in each wave, "What job would you like to do when you grow up?", and a more detailed questionnaire in wave 3 asking about 33 different jobs. Results 9.9 % of children spontaneously mentioned medicine as a career on at least one occasion. For the specific jobs, would-be doctors particularly preferred Hospital Medicine, followed by Surgery, General Practice and then Psychiatry. Would-be doctors were also more interested in careers such as Nurse, Archaeologist, Lawyer and Teacher, and less interested in careers such as Shopkeeper, Sportsperson, or Actor/dancer/singer/musician. Would-be doctors were less Neurotic, more Open to Experience, more Conscientious, and preferred higher prestige occupations. Those interested in medicine did not score more highly on Key Stage 2 attainment tests or Cognitive Abilities Test, did not have a higher family income or greater parental/carer education, and did not have more experience of illness or deaths among family and friends. Conclusions An interest in a medical career, unlike high prestige jobs in general, is not associated with higher educational attainment or cognitive ability, and it is likely that only one in ten of the children interested in medical careers will have sufficient educational attainment at GCSE or A-level to be able to enter medical school.